BRUNO, PAULA. 2011. Pioneros culturales de la Argentina: Biografías de una época. (Colección Metamorfosis). Buenos Aires: Siglo Veintiuno Editores. 240 pp. - Nigro, Malena (2012)
Fil: Nigro, Malena. Universidad de Buenos Aires